An Early Rehabilitation Favors the Prognosis of Hypertensive Intracerebral Hemorrhage With Acute Disorders of Consciousness: A Retrospective Cohort Study With Propensity Score Matching - Rao Xu; Yi Sun; Lin Zhao; Ying Wang; Danjing Yu; Yunxiang Chen; Liqing Bi; Zhiyan Shen; Xintong Zhang; Wei Yan; Xi Wang (Neural Plasticity)
Conclusion: An ER shortens the duration of mechanical ventilation and improves the neurological prognosis in HICH patients with acute DoC. Although the outcome of consciousness is unable to be improved, an ER does reduce the risk of residual cognitive dysfunction in HICH patients with acute DoC.